Simulasi Tekno-Ekonomi Pengembangan Photovoltaic pada Gedung - Sepdian Sepdian; Syafii Syafii (Fakultas Teknik UMRI, 2017)
This research is related to the development of pv system scanning at Politeknik Jambi and economic analysis using RETScreen software. The purpose of this research is to design photovoltaic system at building of Politeknik Jambi, to analyze photovoltaic technology for Poliknik Jambi building and to calculate photovoltaic economy for Politeknik Jambi building. The results showed that the required PV system of 135 kW/day, while based on the results of economic analysis using RETScreen Software required development cost of IDR 4.696.030.000 and capital turnover time for 20 years. This result shows that the system is designed to be built in Politeknik Jambi.